2002
DOI: 10.1117/12.482056
|View full text |Cite
|
Sign up to set email alerts
|

Laser treatment for corrosion prevention

Abstract: The laser surface treatment is applied to a multilayer component (copper alloy plated with two thin coatings, nickel and gold). The aim of the study is to melt the whole gold layer (thick < 1 jim) without damaging the underlying layers. The gold melting must be homogeneous and the process must be fast to avoid heat diffusion in the depth. For these reasons, the laser has been chosen for surface treatment.The application of this laser surface treatment is to improve the corrosion resistance of electrical contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Technique (4) is not universal because it requires that the deposition occurs on preprocessed silicon substrates. The surface of BMs prepared by techniques (1)-( 4) can be easily modied by a localized nanosecond laser treatment that produces a glossy metal surface 27,28 and enables the additional tuning of its functional properties. Technique (5) employs mostly femtosecond lasers 10 and is time consuming, which is its major drawback.…”
Section: Introductionmentioning
confidence: 99%
“…Technique (4) is not universal because it requires that the deposition occurs on preprocessed silicon substrates. The surface of BMs prepared by techniques (1)-( 4) can be easily modied by a localized nanosecond laser treatment that produces a glossy metal surface 27,28 and enables the additional tuning of its functional properties. Technique (5) employs mostly femtosecond lasers 10 and is time consuming, which is its major drawback.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion germs are much smaller than in the untreated area. As detailed in a previous study [7], it is shown that the laser treatment improved the corrosion resistance by reducing the size of the germs. As a general rule, the best results are obtained for a number of pulses ranging from one to five and laser treatment is more efficient on polished samples.…”
Section: Observation Of the Surface Smoothing And Meltingmentioning
confidence: 57%